2011
DOI: 10.3109/09540261.2011.614223
|View full text |Cite
|
Sign up to set email alerts
|

The Use of ECT and MST in treating depression

Abstract: Electroconvulsive therapy (ECT) has been used clinically since 1938. Its most common use is in the treatment of depression: fi rst line treatment where rapid recovery is a priority, but more frequently as an effective treatment for patients who do not respond to pharmacological and psychological approaches. Whilst it is widely hailed as an effective treatment, concerns about its effect on cognition remain. The development of magnetic seizure therapy (MST) over the past decade has attempted to devise a therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(4 citation statements)
references
References 125 publications
(142 reference statements)
0
4
0
Order By: Relevance
“…MST presumably has a better localization of the site of initiation and focalization of propagation [249], which could cause fewer cognitive side effects and possibly have less impact on parasympathetic and sympathetic outflow, which cause HR and BP fluctuation [250]. However, the efficacy of MST in the treatment of depression has not been established [251], although MST has been found to be associated with rapid reorientation and intact anterograde and retrograde memory [252]. Elderly patients may benefit from MST because of its favorable side-effect profile compared with ECT if antidepressant effect of MST is comparable with or superior to ECT, and the treatment becomes FDA approved.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…MST presumably has a better localization of the site of initiation and focalization of propagation [249], which could cause fewer cognitive side effects and possibly have less impact on parasympathetic and sympathetic outflow, which cause HR and BP fluctuation [250]. However, the efficacy of MST in the treatment of depression has not been established [251], although MST has been found to be associated with rapid reorientation and intact anterograde and retrograde memory [252]. Elderly patients may benefit from MST because of its favorable side-effect profile compared with ECT if antidepressant effect of MST is comparable with or superior to ECT, and the treatment becomes FDA approved.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Repeated studies have shown the efficacy of ECT on unipolar as well as bipolar depression [7, 8]. ECT has also been shown effective in a case of catatonia resembling FTD [9].…”
Section: Discussionmentioning
confidence: 99%
“…MST is being investigated as an alternative to ECT for use under general anesthesia with assisted ventilation and continuous electroencephalographic (EEG) monitoring. MST has the potential for fewer side effects, such as cognitive dysfunction, than ECT (Lisanby et al, 2003 ; Allan and Ebmeier, 2011 ), but optimal stimulation parameters for MST are still being investigated. Most studies have used a coil placed at the vertex with a frequency of stimulation of 100 Hz, a pulse width of 0.2–0.4 ms, and a stimulation duration of 10 s (Kito, 2017 ).…”
Section: Adjunctive Biological Options For Treating Trd Alongside Antmentioning
confidence: 99%
“…Most studies have used a coil placed at the vertex with a frequency of stimulation of 100 Hz, a pulse width of 0.2–0.4 ms, and a stimulation duration of 10 s (Kito, 2017 ). There are no large-scale studies comparing MST to sham stimulation and no large-scale controlled studies of relapse following maintenance MST (mMST) with regard to prevention strategies, so the therapy is still in the experimental stage (Allan and Ebmeier, 2011 ).…”
Section: Adjunctive Biological Options For Treating Trd Alongside Antmentioning
confidence: 99%